Full Costing: Sebuah Metode dalam Perhitungan Harga Pokok Produksi - Rahmi, Mega; Aida, Resvina; Maharani, Salsa Nanda; Fadila, Ulfa; Putra, Yosep Eka; Fitri, Sri Adella (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
This study aims to describe the effect of production cost to determine the selling price on the profitability of the Dakak-dakak Ni Nun production business in Nagari Simabur, Pariangan District. This study aims to implement and compile the production cost in the business, where the results of this study can be used as a reference to determine the selling price of the product and how much profit will be obtained. The research method used is a qualitative approach, where data is obtained through interviews with business owners and collection of financial data. This study is expected to contribute to the development of the Dakak-dakak Ni Nun business in Nagari Simabur, Pariangan District, as well as being a reference for other businesses that have similar characteristics.